Hubungan Kerja Lembur dan Shift Kerja dengan Stres Kerja Pada Pekerja Proyek Fit-Out Interior Kantor IFG PT X Jakarta Selatan Tahun 2021 - Gian Jordan (2021)
The workplace had a chance to be workers' source of stress. Work-related stress is a global issue which 54 countries around the world (including Indonesia) faced. Asia Pacific countries have work-related stress trends that exceed the world average statistically. Work-related stress can be affected by overtime work and work shift. The purpose of this study was to determine the association of overtime work and work shift with work stress among workers of IFG Office Fit-Out Interior Project PT X. This was a quantitative analytic research with a cross-sectional design. A total of 47 workers at IFG Office Fit-Out Interior Project PT X were recruited as samples in this study by using a total sampling technique. All data was analyzed using Fisher's Exact test. The results showed that were 38 workers who experienced stress. The results of bivariate analysis showed that overtime work (p-value=0.049 and POR=4.971) and work shift (p-value=0.039 and POR=8.000) were associated with work-related stress. Suggestions for the company are to apply good stress management system and to apply quick overtime work and night shift rotating system. Suggestions for workers are doing stress management program and having a good rest/sleep.